High-Frequency Hearing Loss Is Associated With Anxiety and Brain Structural Plasticity in Older Adults - Ma, Wen; Zhang, Yue; Li, Xiao; Liu, Siqi; Gao, Yuting; Yang, Jing; Xu, Longji; Liang, Hudie; Ren, Fuxin; Gao, Fei; Wang, Yao (Frontiers in Aging Neuroscience, 2022)
Age-related hearing loss (ARHL) is a kind of symmetrical and slow sensorineural hearing loss, which is a common condition in older adults. The characteristic of ARHL is hearing loss beginning in the high-frequency region and spreading towards the low-frequency with age. Previous studies have linked it to anxiety, suggesting that brain structure may be involved in compensatory plasticity after partial hearing deprivation. However, the neural mechanisms of underlying ARHL-related anxiety remain unclear. The purpose of this cross-sectional study was to explore the interactions among high-frequency hearing loss and anxiety as well as brain structure in older adults . Sixty-seven ARHL patients and 68 normal hearing (NH) controls were participated in this study, and the inclusion criterion of ARHL group was four-frequency (0.5, 1, 2, and 4 kHz) pure tone average (PTA) > 25 decibels hearing level of the better hearing ear. All participants performed three-dimensional T1-weighted magnetic resonance imaging (MRI), pure tone audiometry tests, anxiety and depression scales. Our results found gray matter volume (GMV) decreased in 20 brain regions in ARHL group compared with NH group, and a positive correlation existed between high-frequency pure tone audiometry (H-PT) and anxiety scores in ARHL group. Among 20 brain regions, we also found the GMVs of the middle cingulate cortex (MCC) and the hippocampal/parahippocampal (H-P) regions were associated with H-PT and anxiety scores in all participants separately. However, the depressive symptoms indicated no relationship with hearing assessment or GMVs. Our findings revealed that the crucial role of MCC and H-P in a link of anxiety and hearing loss in older adults.